CD99 monoclonal antibody induce homotypic adhesion of Jurkat cells through protein tyrosine kinase and protein kinase C-dependent pathway - Kasinrerk W. (2014)
CD99 is a 32 kDa cell surface glycoprotein which is involved in cell adhesion. Engagement of the CD99 molecule by CD99 monoclonal antibodies has been shown to induce homotypic aggregation of various cell types. By using a newly established CD99 monoclonal antibody, MT99/3, we show here that LFA-1/ICAM-1 independent cell adhesion pathways are activated via CD99. Engagement of the CD99 molecule by MT99/3 induced homotypic cell aggregation of Jurkat T-cells within 30 min reaching its maximal level within 4 h. The Jurkat cell aggregation was not blocked by addition of CD11a (LFA-1) and CD54 (ICAM-1) mAbs. Furthermore, MT99/3 treatment did not alter the expression of LFA-1 and ICAM-1 molecules. Induction of Jurkat homotypic aggregation by MT99/3 was, however blocked by the protein kinase C inhibitor, sphingosine, the protein tyrosine kinase inhibitor, genistein, and by actin filament polymerization blocking agent, cytochalasin B. Thus, these observations suggest that CD99 can mediate beta2-integrin independent cell adhesion that depends on activation of protein kinases and reorganization of the cytoskeleton.